Catalyst components for polymerization of olefins
By using specific combinations of catalyst components, the reactor scaling problem caused by the formation of agglomerates in gas phase polymerization is solved, and the effect of improving the fluidization efficiency of the polymerization reactor and the product packing density is achieved.
Patent Information
- Application Number
- CN202380061916.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-27
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-11
AI Technical Summary
There is a tendency for agglomerates to form in gas phase polymerization, resulting in loss of scaling and fluidization efficiency of the polymerization reactor, especially when small catalyst particles are used.
The catalyst components with specific physical properties, including Ti, Mg and 1,3-diether, are employed as internal donors, with an average particle size D50 ranging from 55 to 80 μm, a specific combination of surface area (SA) and porosity (P), so that the value of SAxD50/100 is higher than 60, preferably higher than 80, further optimized to higher than 110.
Effectively reduce or minimize operational problems during production conversion activities, improve the fluidization efficiency of the polymerization reactor and the bulk density of the product, avoid reactor scaling, and enhance the stability and wide application of the catalyst.
Smart Images

Figure BDA0005284942260000021 
Figure BDA0005284942260000031 
Figure BDA0005284942260000041
Abstract
Description
Technical Field
[0001] The present disclosure relates to diether-based ZN catalyst components having specific physical characteristics to be used in olefin polymerization, particularly in gas phase polymerization. Background Art
[0002] The advantages of using a gas phase polymerization reactor are well known in the art. This polymerization technique allows the production of polymers with valuable properties at relatively low investment costs. In addition, the use of diether-based catalysts is a known alternative to phthalate-based catalysts.
[0003] A known problem that needs to be addressed in gas phase polymerization processes is the tendency to form polymer agglomerates, which can accumulate in various places such as the polymerization reactor and the lines for circulating gas streams. When polymer agglomerates form inside a polymerization reactor, there can be a number of adverse effects. For example, the agglomerates can clog the polymer discharge valve and prevent the polymer from being discharged from the polymerization reactor. In addition, a loss of fluidization efficiency can occur if the agglomerates fall and cover a portion of the reactor internals. This can lead to the formation of larger agglomerates, which can in turn lead to reactor shutdown.
[0004] This problem is exacerbated in the presence of small catalyst particles, which have a lower ability to disperse the heat of polymerization. However, the use of larger catalyst particles may determine the production of polymers with poor morphology and therefore lower bulk density.
[0005] Such problems may also occur in certain types of gas phase reactors, such as for example those described in EP-B1-102195, which comprise two interconnected polymerization zones in which the polymer circulates continuously, one under fast fluidization conditions (riser) and in the other (downcomer) the polymer particles flow downwards in a packing mode in a densified form. A particular situation which is liable to cause fluid dynamic disturbances and which may lead to reactor fouling may be transition operations between the production of different polymer grades and / or the use of different catalysts.
[0006] In order to minimize these problems, a common attempt is to operate the equipment at lower production conditions. However, while this attempt is not always successful in avoiding operating problems, it inevitably translates into reduced equipment productivity.
[0007] Therefore, there is a need for a catalyst suitable for widespread use in gas phase polymerizations that can reduce or minimize operating problems during turnaround activities.
[0008] This problem has been solved by the catalyst components described herein having a specific combination of chemical and physical characteristics. Summary of the invention
[0009] Therefore, the object of the present application is to provide a catalyst component for olefin polymerization, which catalyst component comprises Ti, Mg and an internal donor selected from 1,3-diethers, the solid catalyst component being characterized in that the average particle size D50 is between 55 and 80 μm and the surface area (SA) measured by the BET method is such that the value of the formula SAxD50 / 100 is higher than 60, preferably higher than 80, more preferably higher than 100, and in particular higher than 110. DETAILED DESCRIPTION
[0010] Preferably, the solid catalyst component has an average particle size D50 of 55 to 75 μm, more preferably 55 to 70 μm, and especially 58 to 70 μm.
[0011] Preferably, the catalyst component has a thickness greater than 0.18 cm 3 / g, preferably higher than 0.19cm 3 / g, more preferably 0.20 to 0.25 cm 3 The porosity (P) is 2.17 W / g, and the porosity (P) is measured by the BET method.
[0012] Preferably, the surface area (SA) is 180 to 400 m 2 / g, more preferably 200 to 350 m 2 / g.
[0013] In a preferred embodiment, the value of the formula SAxP is higher than 10, preferably higher than 20, more preferably higher than 25, and especially higher than 40.
[0014] Preferably, all of the above characteristics are relative to the solid catalyst component in non-prepolymerized form.
[0015] The internal donor is preferably selected from 1,3-diethers of formula (I)
[0016]
[0017] Where R I and R II The same or different and are hydrogen or a straight or branched C1-C 18 Hydrocarbon; R III The groups, identical or different from each other, are hydrogen or C1-C 18 Hydrocarbon; R IV The groups are the same or different from each other and have the same III Same meaning, except they cannot be hydrogen; R I To R IV The radicals may each contain heteroatoms selected from halogen, N, O, S and Si.
[0018] Preferably, R IV is an alkyl radical having 1 to 6 carbon atoms, more particularly a methyl radical, and R III The group is preferably hydrogen. In addition, when R I When R is methyl, ethyl, propyl or isopropyl, II It can be ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, isopentyl, 2-ethylhexyl, cyclopentyl, cyclohexyl, methylcyclohexyl, phenyl or benzyl; when R I When it is hydrogen, R II R may be ethyl, butyl, sec-butyl, tert-butyl, 2-ethylhexyl, cyclohexylethyl, diphenylmethyl, p-chlorophenyl, 1-naphthyl, 1-decalinyl; I and R II They may also be the same and may be ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, neopentyl, phenyl, benzyl, cyclohexyl, or cyclopentyl.
[0019] Specific examples of ethers that can be advantageously used include 2-(2-ethylhexyl)-1,3-dimethoxypropane, 2-isopropyl-1,3-dimethoxypropane, 2-butyl-1,3-dimethoxypropane, 2-sec-butyl-1,3-dimethoxypropane, 2-cyclohexyl-1,3-dimethoxypropane, 2-phenyl-1,3-dimethoxypropane, 2-tert-butyl-1,3-dimethoxypropane, 2-cumyl-1,3-dimethoxypropane, 2-(2-phenylethyl)-1,3-dimethoxypropane, 2-(2-cyclohexylethyl)-1,3-dimethoxypropane, 2-(p-chlorophenyl)-1,3-dimethoxypropane, 2-(diphenylmethyl)-1,3-dimethoxypropane, 2-(1-naphthyl)-1 ,3-dimethoxypropane, 2(p-fluorophenyl)-1,3-dimethoxypropane, 2(1-decalinyl)-1,3-dimethoxypropane, 2(p-tert-butylphenyl)-1,3-dimethoxypropane, 2,2-dicyclohexyl-1,3-dimethoxypropane, 2,2-diethyl-1,3-dimethoxypropane, 2,2-dipropyl-1,3-dimethoxypropane, 2,2-dibutyl-1,3-dimethoxypropane, 2,2-diethyl-1,3-diethoxypropane, 2,2-dicyclopentyl-1,3-dimethoxypropane, 2,2-dipropyl-1,3-diethoxypropane, 2,2-dibutyl-1,3-diethoxypropane, 2-methyl-2-ethyl-1,3-dimethoxypropane, 2-methyl 2-propyl-1,3-dimethoxypropane, 2-methyl-2-benzyl-1,3-dimethoxypropane, 2-methyl-2-phenyl-1,3-dimethoxypropane, 2-methyl-2-cyclohexyl-1,3-dimethoxypropane, 2-methyl-2-methylcyclohexyl-1,3-dimethoxypropane, 2,2-bis(p-chlorophenyl)-1,3-dimethoxypropane, 2,2-bis(2-phenylethyl)-1,3-dimethoxypropane, 2,2-bis(2-cyclohexylethyl)-1,3-dimethoxypropane, 2-methyl-2-isobutyl-1,3-dimethoxypropane, 2-methyl-2-(2-ethylhexyl)-1,3-dimethoxypropane, 2,2-bis(2-ethylhexyl)-1,3-dimethoxypropane Oxypropane, 2,2-bis(p-methylphenyl)-1,3-dimethoxypropane, 2-methyl-2-isopropyl-1,3-dimethoxypropane, 2,2-diisobutyl-1,3-dimethoxypropane, 2,2-diphenyl-1,3-dimethoxypropane, 2,2-dibenzyl-1,3-dimethoxypropane, 2-isopropyl-2-cyclopentyl-1,3-dimethoxypropane, 2,2-bis(cyclohexylmethyl)-1,3-dimethoxypropane, 2,2-diisobutyl-1,3-diethoxypropane, 2,2-diisobutyl-1,3-dibutoxypropane, 2-isobutyl-2-isopropyl-1,3-dimethoxypropane, 2,2-di-sec-butyl-1,3-dimethoxypropane, 2,2-di-tert-butyl-1,3-dimethoxypropane, 2,2-neopentyl-1,3-dimethoxypropane, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, 2-phenyl-2-benzyl-1,3-dimethoxypropane, 2-cyclohexyl-2-cyclohexylmethyl-1,3-dimethoxypropane, 2-cyclohexyl-2-isopentyl-1,3-dimethoxypropane.
[0020] Furthermore, particularly preferred are 1,3-diethers of the formula (II)
[0021]
[0022] The group R IV has the same meaning as defined in formula (I) and the group R III and R V The same or different from each other, selected from hydrogen; halogen, preferably Cl and F; linear or branched C1-C 20 Alkyl; C3-C 20 Cycloalkyl, C6-C 20 Aryl, C7-C 20 Alkyl and C7-C 20 An arylalkyl group and two or more R V The groups may be bonded to each other to form a fused ring structure, which is saturated or unsaturated, and is optionally selected from halogen, preferably Cl and F. VI Group substitution; straight chain or branched C l -C 20 Alkyl; C3-C 20 Cycloalkyl, C6-C 20 Aryl, C7-C 20 Alkaryl and C7- C20 Aralkyl; the group R V and R VI Optionally, one or more heteroatoms are contained as substituents for carbon atoms or hydrogen atoms or both.
[0023] Preferably, in the 1,3-diethers of formula (I) and (II), all R III The radical is hydrogen, all R IV Furthermore, particular preference is given to 1,3-diethers of formula (II) in which two or more R V The groups are bonded to each other to form one or more fused ring structures, preferably benzene, optionally with R VI Particularly preferred are compounds of formula (III):
[0024]
[0025] Where R III and R IVThe groups have the same meanings as defined in formula (I), R VI The groups are the same or different and are hydrogen; halogen, preferably Cl and F; straight-chain or branched C l -C 20 Alkyl; C3-C 20 Cycloalkyl, C6-C 20 Aryl, C7-C 20 Alkaryl and C7-C 20 Aralkyl groups optionally contain one or more heteroatoms selected from N, O, S, P, Si and halogen (especially Cl and F) as substituents of carbon atoms or hydrogen atoms or both.
[0026] Specific examples of the compounds contained in formulae (II) and (III) are:
[0027] 1,1-Bis(methoxymethyl)-cyclopentadiene;
[0028] 1,1-Bis(methoxymethyl)-2,3,4,5-tetramethylcyclopentadiene;
[0029] 1,1-Bis(methoxymethyl)-2,3,4,5-tetraphenylcyclopentadiene;
[0030] 1,1-Bis(methoxymethyl)-2,3,4,5-tetrafluorocyclopentadiene;
[0031] 1,1-Bis(methoxymethyl)-3,4-dicyclopentylcyclopentadiene;
[0032] 1,1-bis(methoxymethyl)indene; 1,1-bis(methoxymethyl)-2,3-dimethylindene;
[0033] 1,1-Bis(methoxymethyl)-4,5,6,7-tetrahydroindene;
[0034] 1,1-Bis(methoxymethyl)-2,3,6,7-tetrafluoroindene;
[0035] 1,1-bis(methoxymethyl)-4,7-dimethylindene;
[0036] 1,1-bis(methoxymethyl)-3,6-dimethylindene;
[0037] 1,1-Bis(methoxymethyl)-4-phenylindene;
[0038] 1,1-Bis(methoxymethyl)-4-phenyl-2-methylindene;
[0039] 1,1-Bis(methoxymethyl)-4-cyclohexylindene;
[0040] 1,1-Bis(methoxymethyl)-7-(3,3,3-trifluoropropyl)indene;
[0041] 1,1-Bis(methoxymethyl)-7-trimethylsilaneindene;
[0042] 1,1-Bis(methoxymethyl)-7-trifluoromethylindene;
[0043] 1,1-bis(methoxymethyl)-4,7-dimethyl-4,5,6,7-tetrahydroindene;
[0044] 1,1-Bis(methoxymethyl)-7-methylindene;
[0045] 1,1-Bis(methoxymethyl)-7-cyclopentylindene;
[0046] 1,1-Bis(methoxymethyl)-7-isopropylindene;
[0047] 1,1-Bis(methoxymethyl)-7-cyclohexylindene;
[0048] 1,1-Bis(methoxymethyl)-7-tert-butylindene;
[0049] 1,1-Bis(methoxymethyl)-7-tert-butyl-2-methylindene;
[0050] 1,1-Bis(methoxymethyl)-7-phenylindene;
[0051] 1,1-Bis(methoxymethyl)-2-phenylindene;
[0052] 1,1-Bis(methoxymethyl)-1H-benzo[e]indene;
[0053] 1,1-Bis(methoxymethyl)-1H-2-methylbenzo[e]indene;
[0054] 9,9-bis(methoxymethyl)fluorene;
[0055] 9,9-bis(methoxymethyl)-2,3,6,7-tetramethylfluorene;
[0056] 9,9-bis(methoxymethyl)-2,3,4,5,6,7-hexafluorofluorene;
[0057] 9,9-bis(methoxymethyl)-2,3-benzofluorene;
[0058] 9,9-bis(methoxymethyl)-2,3,6,7-dibenzofluorene;
[0059] 9,9-bis(methoxymethyl)-2,7-diisopropylfluorene;
[0060] 9,9-bis(methoxymethyl)-1,8-dichlorofluorene;
[0061] 9,9-Bis(methoxymethyl)-2,7-dicyclopentylfluorene;
[0062] 9,9-bis(methoxymethyl)-1,8-difluorofluorene;
[0063] 9,9-bis(methoxymethyl)-1,2,3,4-tetrahydrofluorene;
[0064] 9,9-bis(methoxymethyl)-1,2,3,4,5,6,7,8-octahydrofluorene;
[0065] 9,9-Bis(methoxymethyl)-4-tert-butylfluorene.
[0066] Small amounts of additional electron donors other than the diether may also be present. When present, the additional donors are preferably selected from alcohols or monocarboxylic acid esters, and their molar amount is preferably less than 25% of the amount of 1,3-diether.
[0067] Preferably, the molar ratio between 1,3-diether and Ti atoms in the final solid catalyst component is from 0.3:1 to 1.5:1, and more preferably from 0.4:1 to 1.3:1.
[0068] Preferably, the molar ratio between Mg atoms and 1,3-diether in the final solid catalyst component is from 4.0:1 to 25.0:1, and more preferably from 5.0:1 to 20.0:1.
[0069] In a preferred embodiment, the Mg / Ti molar ratio is 2-25, preferably 4-20, especially 5-10.
[0070] In addition to the above-mentioned electron donor, the solid catalyst component also comprises a titanium compound and a magnesium halide with at least a Ti-halogen bond. The magnesium halide is preferably MgCl in active form, which is widely known in the patent literature as a carrier of a Ziegler-Natta catalyst. Patents USP 4,298,718 and USP 4,495,338 first describe the purposes of these compounds in Ziegler-Natta catalysis. From these patents, it is known that the active form of magnesium dihalide used as a carrier or co-carrier in the component of the catalyst for olefin polymerization is characterized by an X-ray spectrum, wherein the intensity of the strongest diffraction line that appears in the spectrum of the inactive halide is reduced, and is replaced by a halogen whose maximum intensity is relative to a stronger line to a lower angle displacement.
[0071] Preferred titanium compounds used in the catalyst components of the present disclosure are TiCl4 and TiCl3; in addition, compounds of the formula Ti(OR) may also be used. n-y X y Ti-haloalcoholate wherein n is the valence of titanium, y is a number between 1 and n-1, X is a halogen, and R is a hydrocarbon group having 1 to 10 carbon atoms.
[0072] The preparation of the solid catalyst component can be carried out according to several methods. According to a preferred method, the solid catalyst component can be prepared by making a 5 ) m-y X y A titanium compound (wherein m is the valence of titanium and y is a number between 1 and m, preferably TiCl4) and a compound derived from the formula MgCl2·pR 6 OH (where p is a number between 1.5 and 4.5, and R 6 According to the preferred method, an adduct between magnesium chloride and an alcohol (especially ethanol) is used, wherein each mole of Mg contains 1.5 to 4.0 moles of alcohol.
[0073] The adduct can be prepared by contacting MgCl2 with an alcohol in the absence of an inert liquid dispersant, heating the system at the melting temperature of the MgCl2-alcohol adduct or higher, and maintaining the conditions to obtain a completely molten adduct. In particular, the adduct is preferably maintained at a temperature equal to or higher than its melting temperature under stirring conditions for a period of equal to or greater than 1 hour, preferably 2 to 15 hours, more preferably 5 to 10 hours. The molten adduct is then emulsified in a liquid medium that is immiscible therewith and chemically inert thereto, and finally quenched by contacting the adduct with an inert cooling liquid, thereby achieving solidification of the adduct. Before recovering the solid particles, they are also preferably left in the cooling liquid at a temperature of -10 to 25°C for a period of 1 to 24 hours.
[0074] In a variant of this method, the MgCl particles can be dispersed in an inert liquid immiscible with the molten adduct and chemically inert thereto, the system is heated at a temperature equal to or higher than the melting temperature of the MgCl ethanol adduct, and then the desired amount of alcohol in the gas phase is added. The temperature is maintained at a value that completely melts the adduct for a period of 10 minutes to 10 hours. The molten adduct is then processed as disclosed above. The liquid in which the MgCl is dispersed or the adduct is emulsified can be any liquid immiscible with the molten adduct and chemically inert thereto. For example, aliphatic, aromatic or cycloaliphatic hydrocarbons and silicone oils can be used. Aliphatic hydrocarbons such as vaseline are particularly preferred.
[0075] The quenching liquid is preferably selected from hydrocarbons that are liquid in the temperature range of -30 to 30° C. Among them, pentane, hexane, heptane or a mixture thereof is preferred.
[0076] In both methods, the desired particle size of the final adduct is obtained by appropriately setting the fluid dynamic parameters controlling the formation of the adduct droplet size (Reynolds number, type of rotor-stator system, etc.), which are related to the size of the solid particles, according to techniques known in the art and disclosed, for example, in WO 02 / 051544 (in particular on pages 6 to 7).
[0077] In a preferred embodiment, the adduct thus obtained contains 3 to 4.5 mol of ethanol per mol of Mg.
[0078] The porosity of the solidified adduct particles can be increased by a dealcoholation step, carried out according to known methods, such as the method described in EP-A-395083, in which the dealcoholation is obtained by keeping the adduct particles in a fluidized bed formed by a flow of warm nitrogen, which is directed out of the system after removing the alcohol from the adduct particles. The dealcoholation treatment can be carried out under an increasing temperature gradient until the particles have reached the desired alcohol content, which in any case is at least 10% (molar) lower than the initial amount.
[0079] In a preferred method according to the present disclosure, the dealcoholation treatment is carried out until the number of moles of alcohol per mole of Mg is from 1.5 to less than 3.5, preferably from 1.5 to 3.0.
[0080] In a preferred method for producing the catalyst of the present invention, the reaction with the Ti compound can be carried out by suspending the adduct (de-alcoholated or as is) in TiCl4 at a temperature of 0°C or lower, particularly at -2°C to -15°C, and more preferably at -3°C to -10°C. Preferably, the adduct is used in an amount so as to have a concentration of from 20 to 80 g / l, preferably from 30 to 60 g / l, and especially from 35 to less than 55 g / l. According to a preferred embodiment, the electron donor (I) is added to the system at the beginning of the reaction phase and preferably when the temperature of the mixture is in the range of 10°C to 60°C. The electron donor (I) is fed in an amount such that the desired molar ratio in the final catalyst is met. In one embodiment, the Mg / donor (I) molar ratio can be from 2:1 to 15:1, and preferably from 3:1 to 10:1. The temperature is then gradually increased until a temperature of 90 to 130°C is reached and maintained at this temperature for 0.5 to 3 hours.
[0081] After the reaction time is over, stirring is stopped, the slurry is allowed to settle, and the liquid phase is removed. A second stage of treatment with TiCl4 is performed, preferably at a temperature ranging from 70 to 130°C. After the reaction time is over, stirring is stopped, the slurry is allowed to settle, and the liquid phase is removed. Although not essential, additional reaction stages may be performed with titanium compounds, and preferably with TiCl4, under the same conditions described above and in the absence of an electron donor. The solid thus obtained may then be washed with a liquid hydrocarbon under mild conditions and then dried.
[0082] The solid catalyst component may also contain small amounts of additional metal compounds selected from those containing elements belonging to Groups 1 to 15, preferably Groups 11 to 15, of the Periodic Table of the Elements (Iupac version).
[0083] Most preferably, the compound comprises an element selected from Cu, Zn and Bi that does not contain a metal-carbon bond. Preferred compounds are oxides, carbonates, alkoxides, carboxylates and halides of the metals. Among them, ZnO, ZnCl2, CuO, CuCl2 and Cu diacetate, BiCl 3、 Bi carbonate and Bi carboxylate. BiCl is particularly preferred. 3、 Bi carbonates and Bi carboxylates.
[0084] The compounds may be added during the preparation of the aforementioned magnesium-alcohol adduct, or they may be introduced into the catalyst by dispersing them in the titanium compound in liquid form and then reacting with the adduct.
[0085] Whichever method is used, the final amount of said metal going into the final catalyst component ranges from 0.1 to 10 wt%, preferably from 0.3 to 8 wt% and most preferably from 0.5 to 5 wt% relative to the total weight of the solid catalyst component.
[0086] The solid catalyst components according to the present disclosure are used for the polymerization of olefins by reacting them with organoaluminum compounds according to known methods.
[0087] In particular, the present disclosure is directed to catalysts for the polymerization of olefins CH2=CHR, wherein R is hydrogen or C1-C 12 Hydrocarbyl, comprising the reaction products of:
[0088] (i) the solid catalyst component of the present disclosure and
[0089] (ii) an alkylaluminum compound and, optionally,
[0090] (iii) External electron donor compounds.
[0091] The alkyl-Al compound (ii) is preferably selected from trialkylaluminum compounds, such as, for example, triethylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum. It is also possible to use a mixture of a trialkylaluminum with an alkylaluminum halide, an alkylaluminum hydride or an alkylaluminum sesquichloride (such as AlEt2Cl and Al2Et3Cl3).
[0092] Preferably, the alkylaluminum compound is used in the gas phase process in such an amount that the Al / Ti molar ratio is from 10 to 400, preferably from 30 to 250, more preferably from 40 to 200.
[0093] As mentioned above, the catalyst system may include an external electron donor (ED) selected from several classes. Among ethers, preferred are 1,3 diethers also disclosed as internal donors in the solid catalyst component (a). Among esters, preferred are esters of aliphatic saturated mono- or dicarboxylic acids, such as malonates, succinates and glutarates. Among heterocyclic compounds, 2,2,6,6-tetramethylpiperidine is particularly preferred. A particularly preferred class of external donor compounds are silicon compounds having at least one Si-OC bond. Preferably, the silicon compound has the formula Ra 5 R 6 Si(OR 7 )c, wherein a and b are integers from 0 to 2, c is an integer from 1 to 3 and the sum of (a+b+c) is 4; R 5 , R 6 and R 7 is an alkyl, cycloalkyl or aryl group having 1 to 18 carbon atoms, optionally containing heteroatoms selected from N, O, halogen and P. Particularly preferred are methylcyclohexyldimethoxysilane, diphenyldimethoxysilane, methyltert-butyldimethoxysilane, dicyclopentyldimethoxysilane, 2-ethylpiperidinyl-2-tert-butyldimethoxysilane and 1,1,1-trifluoropropyl-2-ethylpiperidinyl-dimethoxysilane and 1,1,1-trifluoropropyl-methyl-dimethoxysilane. The amount of the external electron donor compound used is such that the molar ratio between the organoaluminum compound and the electron donor compound is from 2 to 500, preferably from 5 to 350, more preferably from 7 to 200, especially from 7 to 150.
[0094] The solid catalyst component of the present disclosure is suitable for direct use in polymerization together with a cocatalyst.Although prepolymerization is not necessary, it can be performed by subjecting the solid catalyst component to prepolymerization conditions in the presence of an olefin monomer and an Al-alkyl compound.
[0095] The term "prepolymerization conditions" refers to the combination of conditions in terms of temperature, monomer feed, and amounts of reagents suitable for preparing a prepolymerized catalyst component containing from 0.1 to 500 g of polymer per gram of catalyst.
[0096] The cocatalyst used in the prepolymerization may be the same alkyl-Al compound (ii) as described above.
[0097] The prepolymerization can be carried out in-line, i.e. in one of the reactors of a cascade polymerization process, or it can be carried out in batches. In the latter process, the final prepolymerized catalyst is recovered, separated and then used in a separate polymerization process.
[0098] In the case of batch prepolymerization, it has been found to be particularly advantageous to use small amounts of alkyl-Al compounds. In particular, the amount may be such that the Al compound / catalyst weight ratio is from 0.001 to 10, preferably from 0.005 to 5, and more preferably from 0.005 to 1.5.
[0099] The prepolymerization can be carried out with any α-olefin, in particular selected from the group consisting of ethylene, propylene, butene-1, 4-methyl-pentene-1, hexene-1 and octene-1.
[0100] The prepolymerization step can be carried out in liquid or gas phase at a temperature of from 0 to 80° C., preferably from 5 to 50° C. It is particularly preferred that the catalyst of the invention is batch prepolymerized with ethylene to produce an amount of polymer of 0.5 to 20 g per gram of catalyst component.
[0101] It is also possible to use an external donor selected from the group consisting of previously reported silicon compounds of the general formula (I), ethers, esters, amines, heterocyclic compounds, ketones and 1,3-diethers. However, the use of an external donor in the prepolymerization is not strictly necessary.
[0102] The prepolymerization can be carried out in the liquid phase (slurry or bulk) or in the gas phase at a temperature of typically -20 to 80°C, preferably 0°C to 75°C. Preferably, it is carried out in a liquid diluent, in particular selected from liquid light hydrocarbons. Among them, pentane, hexane and heptane are preferred. In an alternative embodiment, the prepolymerization can be carried out in a more viscous medium, in particular in a medium having a kinematic viscosity of 5 to 100 cSt at 40°C. This medium can be a pure substance or a homogeneous mixture of substances with different kinematic viscosities. Preferably, this medium is a hydrocarbon medium, and more preferably, it has a kinematic viscosity of 10 to 90 cSt at 40°C.
[0103] The olefin monomer to be prepolymerized may be fed into the reactor in a predetermined amount and in a step prior to the prepolymerization. In an alternative embodiment, the olefin monomer is continuously supplied to the reactor at a desired rate during the polymerization.
[0104] The catalyst disclosed in the present invention is suitable for any polymerization technology, especially for gas phase polymerization. The gas phase process can be carried out with any type of gas phase reactor. Specifically, it can be operated in one or more fluidized beds or mechanically stirred bed reactors. In a fluidized bed reactor, fluidization is obtained by an inert fluidizing gas flow, the speed of which is not higher than the conveying speed. Therefore, a fluidized particle bed can be found in a more or less restricted area of the reactor. In a mechanically stirred bed reactor, the polymer bed is kept in place by a gas flow generated by continuous blade movement, and the regulation of the blade movement also determines the height of the bed. The operating temperature can be between 50 and 85°C, preferably between 60 and 85°C, and the operating pressure can be between 0.5 and 8MPa, preferably between 1 and 5MPa, more preferably between 1.0 and 3.0MPa. Inert fluidizing gas can also be used to dissipate the heat generated by the polymerization reaction, and can be selected from nitrogen or preferably saturated light hydrocarbons such as propane, pentane, hexane or mixtures thereof.
[0105] The polymer molecular weight can be controlled by using an appropriate amount of hydrogen or any other molecular weight regulator such as ZnEt2. If hydrogen is used, the hydrogen / propylene molar ratio can be 0.0002-0.5, and the propylene monomer accounts for 20-100 volume %, preferably 30-70 volume %, based on the total volume of the gas present in the reactor. The remainder of the feed mixture consists of inert gas and one or more alpha-olefin comonomers (if any).
[0106] The catalyst disclosed herein is particularly suitable for gas phase polymerization technology comprising at least two interconnected polymerization zones. The method is carried out in an interconnected first polymerization zone and a second polymerization zone, propylene and ethylene or propylene and α-olefins are fed into the first polymerization zone and the second polymerization zone in the presence of a catalyst system, and the produced polymer is discharged from the first polymerization zone and the second polymerization zone. The growing polymer particles flow through the first polymerization zone (riser) under fast fluidization conditions, leave the first polymerization zone and enter the second polymerization zone (downcomer), they flow through the second polymerization zone in a densified form under the action of gravity, leave the second polymerization zone and reintroduce the first polymerization zone, thereby establishing a circulation of the polymer between the two polymerization zones. The fast fluidization conditions in the first polymerization zone can be established by feeding the monomer gas mixture to a point lower than the point at which the growing polymer is reintroduced into the first polymerization zone. The velocity of the conveying gas entering the first polymerization zone is higher than the conveying velocity under operating conditions, preferably 2- to 15 m / s. In the second polymerization zone, in which the polymer flows in a densified form under the action of gravity, a high solid density value close to the bulk density of the polymer is reached; a positive pressure gain can therefore be obtained along the flow direction, making it possible to reintroduce the polymer into the first reaction zone without the aid of mechanical means. In this way, a "loop" circulation is established, which is defined by the pressure balance between the two polymerization zones and the head loss introduced into the system. In this case as well, one or more inert gases, such as nitrogen or aliphatic hydrocarbons, are maintained in the polymerization zone in an amount such that the sum of the partial pressures of the inert gases is preferably 5-80% of the total gas pressure. The operating temperature is 50-85°C, preferably 60-85°C, and the operating pressure is 0.5-10Mpa, preferably 1.5-6MPa. Preferably, the catalyst components are fed to the first polymerization zone at any point in the first polymerization zone. However, they can also be fed at any point in the second polymerization zone. The use of a molecular weight regulator is carried out under the aforementioned conditions. By using the device described in WO00 / 02929, it is possible to completely or partially prevent the gas mixture present in the riser from entering the downcomer; in particular, this is preferably obtained by introducing in the downcomer a gas and / or liquid mixture having a composition different from that of the gas mixture present in the riser. According to a particular embodiment of the present disclosure, introducing into the downcomer said gas and / or liquid mixture having a composition different from that of the gas mixture present in the riser effectively prevents the latter mixture from entering the downcomer. Thus, it is possible to obtain two interconnected polymerization zones having different monomer compositions and thus being able to produce polymers having different properties.
[0107] As shown in the examples, the catalysts of the present disclosure allow for smooth transitions when changing polymerization conditions, as evidenced by the low temperature difference between the reactor wall and the reactor interior. In particular, the catalyst components of the present disclosure exhibit the above capabilities as well as high polymerization activity, and the ability to produce various types of propylene polymers, such as homopolymers, random copolymers and heterophasic copolymers, having high bulk densities, in particular exceeding 0.40 and preferably exceeding 0.42 g / cm 3 The polymers produced have a melt flow rate of 0.1 to 100 g / 10', preferably 1 to 70 g / 10', making them suitable for a wide variety of end-use applications.
[0108] Example
[0109] The following examples are given to better illustrate the present disclosure but are not intended to limit the present disclosure in any way.
[0110] Characterization
[0111] Determination of XI
[0112] 2.5 g of polymer was dissolved in 250 ml of o-xylene with stirring at 135° C. for 30 minutes, then the solution was cooled to 25° C. and the insoluble polymer was filtered after 30 minutes. The resulting solution was evaporated in a nitrogen stream, the residue was dried and weighed to determine the percentage of soluble polymer, and then the XI% was determined by difference.
[0113] Average particle size of adduct and catalyst
[0114] Determined by a method based on the principle of optical diffraction of monochromatic laser light with a "Malvern Instr. 2600" apparatus. The average size is given as D50, defined as the diameter value below which 50% of the particles occupying the total volume have a diameter.
[0115] Bulk density ASTM D 1895 / 96 Method A
[0116] Melt flow rate (MFR) Determined according to ISO 1133 (230°C, 2.16Kg)
[0117] Porosity and surface area using nitrogen
[0118] Porosity and surface area with nitrogen: Determined according to the BET method (using a SORPTOMATIC 1900 apparatus from Carlo Erba).
[0119] Porosity and surface area using mercury :
[0120] The measurements were performed using the "Porosimeter 2000 Series" by Carlo Erba. Porosity was determined by the absorption of mercury under pressure. For this determination, a calibrated dilatometer (3 mm in diameter) CD3 (Carlo Erba) connected to a mercury reservoir and a high vacuum pump (1.10-2 mbar) was used. The weighed sample was placed in the dilatometer. The device was then placed under a high vacuum (<0.1 mm Hg) and kept under these conditions for 20 minutes. The dilatometer was then connected to the mercury reservoir, and mercury was allowed to flow slowly into the dilatometer until it reached the level marked on the dilatometer at a height of 10 cm. The valve connecting the dilatometer and the vacuum pump was closed, and the mercury pressure was then gradually increased with nitrogen until 140 kg / cm 2 Under pressure, the mercury enters the pores and descends according to the porosity level of the material.
[0121] Porosity (cm 3 / g), since the pores of the catalyst are up to 1 μm (the pores of the polymer are up to 10 μm), the pore distribution curve and the average pore size are calculated directly from the integrated pore distribution curve, which is a function of the volume reduction of mercury and the value of the applied pressure (all these data are provided and elaborated by the porosimeter associated computer, which is equipped with the "MILESTONE 200 / 2.04" program provided by C. Erba).
[0122] General Procedure for Propylene Polymerization Experiments
[0123] The propylene copolymer composition in the example is prepared in a single gas phase polymerization reactor, which includes two interconnected polymerization zones (riser and downcomer), as described in the general polymerization procedure section of WO00 / 02929, except that barrier agent feeding is not implemented. In order to measure the temperature difference between the wall temperature and the inside of the reactor during the conversion, the reactor is equipped with a pair of thermal probes located at the bottom of the downcomer. Triethylaluminum (TEAL) is used as a cocatalyst and dicyclopentyldimethoxysilane is used as an external donor, and the weight ratio is shown in the example. Starting from certain operating conditions, in order to produce the specific polymer grade shown in each example, the polymerization conditions are changed to different polymer grades. During the conversion time, the temperature difference between the reactor wall and the inside of the reactor is measured to evaluate smooth operability.
[0124] Example
[0125] Example 1
[0126] Catalyst carrier
[0127] In a vessel reactor equipped with an IKA RE 166 stirrer, containing 183.5 g of anhydrous EtOH at a temperature of -8°C, 100 g of MgCl2 and 3.2 g of water were introduced under stirring. After the addition of MgCl2 was complete, the temperature was raised to 108°C and maintained at this value for 20 hours. Thereafter, while the temperature was maintained at 108°C, the melt was fed together with OB55 oil into an emulsifier operating at 1500 rpm by a positive displacement pump set at 260 ml / min and a positive displacement pump set at 1100 ml / min, respectively, to produce an emulsion of melt and oil. While the melt and oil were continuously fed, the mixture at about 108°C was continuously discharged into a vessel containing 5 liters of cold hexane, with constant stirring and cooling, so that the final temperature did not exceed 12°C. After 24 hours, the solid particles of the adduct recovered were then washed with hexane and dried in vacuo at 40°C to obtain a D50 diameter of 68.6 μm. The adduct was then thermally dealcoholated in a fluidized bed under a nitrogen flow at elevated temperature until the EtOH content reached a chemical composition of 50.2 wt % EtOH and 1.4 wt % H2O, the remainder being MgCl2.
[0128] Preparation of final catalyst components
[0129] 1.0l TiCl4 was introduced into a 2.0 liter round-bottom flask equipped with a mechanical stirrer, a cooler and a thermometer at room temperature under a nitrogen atmosphere. After cooling to -5°C, 54g of microspheres prepared as described above were introduced while stirring. The temperature was then raised from -5°C to 40°C at a rate of 0.3°C / min, and a certain amount of 9,9-bis(methoxymethyl)fluorene was added so that the Mg / diether molar ratio was 8. The temperature was then raised to 100°C and maintained for 50 minutes. The treatment with TiCl4 was repeated at 110°C for 50 minutes, wherein the Mg / diether molar ratio was increased by 21 (total molar ratio of 5.8), and then treated at 110°C for another 30 minutes. The solid was then washed five times (5 times, 900ml each time) with anhydrous hexane at 60°C.
[0130] The solid was finally dried under vacuum and analyzed. The particle size of the final catalyst component was 67.3 μm and the surface area (BET) was 284 m 2 / g, and the porosity (BET) is 0.213 cm 3 / g.
[0131] In terms of the catalyst composition, the content of Ti was 4.2% by weight, and the content of 9,9-bis(methoxymethyl)fluorene was 16.8% by weight.
[0132] Polymerization (homopolymer-random copolymer conversion)
[0133] In a reactor set up as described in the General Procedure, a first propylene homopolymer having the characteristics reported in Table 1 was prepared under the polymerization conditions reported in the table.
[0134] Table 1
[0135] TEAL / Catalyst Weight Ratio 6 TEAL / Donor Weight Ratio 8 Prepolymerization ℃ / barg T 30 <![CDATA[H2 / C3 - ]]> ℃ --- polymerization T–P ℃-barg 75–28 Yield kg / g 60 <![CDATA[H2 / C3 - ]]> mol / mol 0.0075 Polymer Analysis MFR dg / min 6.6 <![CDATA[C2 - ]]> weight% --- XS weight% 2.5 PBD <![CDATA[kg / dm 3 ]]> 0.426 P50 μm 2513 <500 weight% 1.2–1.8
[0136] The conversion to propylene copolymer grade was initiated by introducing ethylene in the gaseous reactor mixture in order to produce copolymers with the reported characteristics at steady state under the following reaction conditions.
[0137] Table 2
[0138] TEAL / Catalyst Weight Ratio 6 TEAL / Donor Weight Ratio 8 Prepolymerization ℃ / barg T 30 <![CDATA[H2 / C3 - ]]> ℃ --- polymerization T–P ℃-barg 75–28 Yield kg / g 70 <![CDATA[H2 / C3 - ]]> mol / mol 0.0070 <![CDATA[C2 / C2 - +C3 - ]]> mol / mol 0.018 Polymer Analysis MFR dg / min 6.8 <![CDATA[C2 - ]]> weight% 1.8 XS weight% 4.45 PBD <![CDATA[kg / dm 3 ]]> 0.425 P50 μm 2755 <500 weight% 0.4
[0139] The changeover time lasted about three hours. At the start of the changeover, the temperature difference between the reactor surface and the inside of the downcomer bottom was 7.8° C. During the changeover, the temperature difference reached 9.1° C., so the maximum difference was 1.3° C.
[0140] Comparative Example 1
[0141] The same polymerization procedure and switch time were repeated except that the catalyst used was prepared as follows.
[0142] Catalyst support preparation
[0143] An initial amount of MgCl2.2.8C2H5OH adduct was prepared according to the method described in Example 2 of PCT Publication No. WO 98 / 44009, but operated on a larger scale.
[0144] The adduct was then thermally dealcoholated under a nitrogen flow at elevated temperature until the EtOH content reached a chemical composition of 49.7 wt% EtOH and 1.2 wt% water and a particle size D50 of 52.0 μm.
[0145] Preparation of final catalyst components
[0146] 1.0l TiCl4 was introduced into a 2.0 liter round-bottom flask equipped with a mechanical stirrer, a cooler and a thermometer at room temperature under a nitrogen atmosphere. After cooling to 0°C, 50g of microspheres prepared as disclosed in the general procedure were introduced while stirring. The temperature was then raised from 0°C to 40°C at a rate of 0.4°C / min, and a certain amount of 9,9-bis(methoxymethyl)fluorene was added so that the Mg / diether molar ratio was 5. The temperature was then raised to 100°C and maintained for 50 minutes. The treatment with TiCl4 was repeated at 109°C for 20 minutes and then at 109°C for 15 minutes. The solid was then washed five times (5 times, 900ml each time) with anhydrous hexane at 50°C.
[0147] The solid was finally dried under vacuum and analyzed. The particle size of the final catalyst component was 53.7 μm and the surface area (BET) was 65 m 2 / g.
[0148] In terms of the catalyst composition, the content of Ti was 4.3% by weight, and the content of 9,9-bis(methoxymethyl)fluorene was 15.4% by weight.
[0149] Polymerization (homopolymer-random copolymer conversion)
[0150] The same polymerization procedure and switchover time were carried out as in Example 1. At the start of the switchover, the temperature difference between the reactor surface and the inside of the downcomer bottom was -1.3° C. During the switchover, the temperature difference reached 6.4° C., so that the maximum difference was 7.7° C.
[0151] Example 2
[0152] Preparation of final catalyst components
[0153] 1.0 l TiCl4 was introduced into a 2.0 liter round-bottom flask equipped with a mechanical stirrer, a cooler and a thermometer at room temperature under a nitrogen atmosphere. After cooling to -5°C, 45 g of the microsphere adduct prepared as described in Example 1 were introduced while stirring. The temperature was then raised from -5°C to 40°C at a rate of 0.3°C / min, and a certain amount of 9,9-bis(methoxymethyl)fluorene was added so that the Mg / diether molar ratio was 8. The temperature was then raised to 100°C and maintained for 45 minutes. The treatment with TiCl4 was repeated at 109°C for 45 minutes, the Mg / diether molar ratio was increased by 21, and then a third treatment was carried out at 109°C for 25 minutes. The solid was then washed five times with anhydrous hexane at 50°C (5 times, 900 ml each time).
[0154] The solid was finally dried under vacuum and analyzed. The particle size of the final catalyst component was 66.5 μm and the surface area (BET) was 174 m 2 / g, and the porosity (BET) is 0.183cm 3 / g.
[0155] In terms of the catalyst composition, the content of Ti was 4.2% by weight, and the content of 9,9-bis(methoxymethyl)fluorene was 17.9% by weight.
[0156] Polymerization (random low MFR-random high MFR conversion)
[0157] In a reactor set up as described in the General Procedure, a first propylene ethylene copolymer was prepared under the polymerization conditions reported in Table 3 having the characteristics reported in that table.
[0158] Table 3
[0159]
[0160]
[0161] The switch to propylene ethylene copolymer grades with higher melt flow rates was initiated by increasing the hydrogen feed in the gaseous reactor mixture in order to produce copolymers with the reported characteristics at steady state under the following reaction conditions.
[0162] Table 4
[0163] TEAL / Catalyst Weight Ratio 6 TEAL / Donor Weight Ratio 8 Prepolymerization ℃ / barg T 30 <![CDATA[H2 / C3 - ]]> ℃ --- polymerization T–P ℃-barg 75–28 Downcomer speed m / s 0.211 Yield kg / g 76 <![CDATA[H2 / C3 - ]]> mol / mol 0.0304 <![CDATA[C2 / C2 - +C3 - ]]> mol / mol 0.025 Polymer Analysis MFR dg / min 42 <![CDATA[C2 - ]]> weight% 3.2- XS weight% 7.3 PBD <![CDATA[kg / dm 3 ]]> 0.422 P50 μm 2936 <500 weight% 0.7-1.0
[0164] The changeover time lasted about five hours. At the start of the changeover, the temperature difference between the reactor surface and the inside of the downcomer bottom was 6.0°C. During the changeover, the temperature difference reached 5.5°C, so the maximum difference was -0.5°C. The production of copolymer grade was completed and no reactor fouling was observed.
[0165] Comparative Example 2
[0166] The same polymerization procedure and transfer conditions used in Example 2 were repeated, except that the catalyst of Comparative Example 1 was used. At the beginning of the transfer, the temperature difference between the reactor surface and the inside of the downcomer bottom was 2.0° C. At the end of the transfer, the temperature difference reached 11.3° C., so the maximum difference was 9.3° C. Inspection of the reactor at the end of production revealed the presence of a large amount of fouling.
Claims
1. A solid catalyst component for olefin polymerization, comprising Ti, Mg and an internal donor selected from 1,3-diethers, characterized in that the average particle size (D50) measured by the optical diffraction method reported in this specification is 55 to 80 μm, and the surface area (SA) determined by the BET method reported in this specification is such that the value of the formula SAxD50 / 100 is higher than 60.
2. The solid catalyst component according to claim 1, wherein the value of the formula SAxD50 / 100 is higher than 80.
3. The solid catalyst component according to claim 2, wherein the value of the formula SAxD50 / 100 is higher than 100.
4. A solid catalyst component according to any one of the preceding claims, having an average particle size D50 of 55 to 75 μm.
5. A solid catalyst component according to any one of the preceding claims, having a carbon content higher than 0.18 cm 3 / g, preferably higher than 0.19cm 3 The porosity (P) of 1.17 W / g is measured by the BET method reported in this specification.
6. A solid catalyst component according to any one of the preceding claims, wherein the surface area (SA) is from 180 to 400 m 2 / g.
7. The solid catalyst component according to claim 6, wherein the surface area (SA) is 200 to 350 m 2 / g.
8. A solid catalyst component according to any one of the preceding claims, wherein the value of the formula SAxP is higher than 10.
9. The solid catalyst component according to claim 8, wherein the value of the formula SAxP is higher than 20.
10. A solid catalyst component according to any one of the preceding claims, wherein the 1,3-diether is selected from compounds of formula (I) Where R I and R II The same or different and are hydrogen or a straight or branched C1-C 18 Hydrocarbon; R III The groups, identical or different from each other, are hydrogen or C1-C 18 Hydrocarbon; R IV The groups are the same or different from each other and have the same III Same meaning, except they cannot be hydrogen; R I To R IV The radicals may each contain heteroatoms selected from halogen, N, O, S and Si.
11. The solid catalyst component according to claim 9, wherein the 1,3-diether is selected from those of formula (III): Where R III and R IV The groups have the same meanings as defined in formula (I), R VI The groups are the same or different and are hydrogen; halogen, preferably Cl and F; straight or branched C1-C 20 Alkyl; C3-C 20 Cycloalkyl, C6-C 20 Aryl, C7-C 20 Alkaryl and C7-C 20 Aralkyl groups optionally contain one or more heteroatoms selected from N, O, S, P, Si and halogen (especially Cl and F) as substituents of carbon atoms or hydrogen atoms or both.
12. A catalyst system for the polymerization of olefins CH2=CHR, wherein R is hydrogen or a hydrocarbon radical having 1 to 12 carbon atoms, comprising the reaction product of: (i) a solid catalyst component according to any one of the preceding claims, (ii) an alkylaluminum compound, and optionally, (iii) External electron donor compounds.
13. The catalyst system according to claim 12, wherein the external electron donor is selected from the group consisting of: a 5 R b 6 Si(OR 7 ) c A silicon compound wherein a and b are integers from 0 to 2, c is an integer from 1 to 3 and the sum of (a+b+c) is 4; R 5 , R 6 and R 7 is an alkyl, cycloalkyl or aryl group having 1 to 18 carbon atoms, optionally containing heteroatoms selected from N, O, halogen and P.
14. A gas phase process for the polymerization of olefins CH2=CHR, wherein R is hydrogen or C1-C 12 Hydrocarbyl, the gas phase process being carried out in the presence of a catalyst system according to any one of claims 12 to 13.
15. Gas phase process according to claim 14, which is carried out in a reactor comprising at least a first polymerization zone and a second polymerization zone which are interconnected, wherein polymer particles flow through the first polymerization zone (riser) under fast fluidization conditions, leave the first polymerization zone and enter the second polymerization zone (downcomer), and the polymer particles flow through the second polymerization zone in a densified form under the effect of gravity, thereby establishing a circulation of the polymer between the two polymerization zones.
Citation Information
Patent Citations
Components and catalysts for the polymerization of olefins
EP0395083A2
Method of providing welfare information
EP1102195A2
Magnesium dichloride-alcohol adducts, process for their preparation and catalyst components obtained therefrom
WO1998044009A1
Process and apparatus for the gas-phase polymerisation
WO2000002929A1
Process for the preparation of a spherical support comprising a MG dihalide
WO2002051544A1